Axial length and choriocapillaris flow deficits in non-pathological high myopia - Cheng, Weijing; Song, Yunhe; Gao, Xinbo; Lin, Fengbin; Li, Fei; Wang, Peiyuan; Hu, Kun; Li, Hao; Li, Yingjie; Chen, Lina; Jonas, Jost B.; Wang, Wei; et al. (American journal of ophthalmology, 2022)
Purpose - To examine the relationship between axial length (AL) and choriocapillaris (CC) flow deficits percentage (FD%) in non-pathological highly myopic eyes. - Design - Prospective cross-sectional study. - Methods - This study included Chinese patients with non-pathological high myopia, which was defined by an AL of > 26 mm and a META-PM classification grade of <2. Swept-source optical coherence tomography angiography was used to obtain 6 × 6 mm images of the macular CC. The CC FD% was measured in the fovea, parafovea, and perifovea subfields. - Results - A total of 1017 individuals (1017 eyes) with a mean age of 35.95 ± 14.11 years were included. After adjusting for age, sex, intraocular pressure, body mass index, systolic blood pressure, and image quality score, the overall CC FD% increased by 0.27% (95% CI 0.02, 0.52; P = .034) for each mm increase in AL. Among subfields, longer AL was associated with a higher CC FD% in the perifovea (β = 0.53, 95% CI 0.30, 0.77; P < .001), and was not associated with a higher CC FD% in the parafovea (β = 0.08, 95% CI -0.26, 0.42; P = .652) and fovea (β = 0.001, 95% CI -0.50, 0.50; P = .999). - Conclusions - The CC FD% increased with a longer AL in high myopia in the perifovea region but not in the fovea and parafovea fields. These findings may be of interest in elucidating the etiology of myopic axial elongation.
Gesehen am 23.05.2023